Erratum: Can water float on oil? (Langmuir) - Phan, C.; Allen, B.; Peter, L.; Le, T.; Tade, Moses (2012)
Equations 3−5 in the original paper were wrongly written because of changes in notation during manuscript preparation. These mistakes do not affect the modeling results.